Study of Multiple Regression Modal between Soil Properties and Colony-forming Unit Collected from Diverse Regions of Rajasthan, India - Himanshi Mangla; Saurabh Dave; Smita Jain; Hardik Pathak (International Journal of Environmental Health Engineering)
Aim: This study was done to predict the relation between soil properties and colony-forming unit (CFU) at different landscape positions from observed values using simplified regression models. Methods: Soil samples (normal and petroleum contaminated) were collected from diverse regions of Rajasthan, India. The coefficient of correlation was calculated between the CFU and the physicochemical properties of soils such as pH, conductivity, moisture content, organic matter, and heavy metals. Before applying the regression models, the dependency of several soil properties with CFU, the principal component (PC) analysis, was applied. Results: As a result, only three PCs have eigenvalues >1. In the regression analysis of variance, the P value is found to be >0.05, so the regression model is significant. Conclusion: This approach would promote soil sampling and variable rate application of agricultural chemicals and would serve as a fast, inexpensive, and reasonably accurate method to develop a soil database for fields that have similar soil characteristics.